Illusory movements for immobile patients with extensive burns (IMMOBILE): A randomized, controlled, cross-over trial - Bakalář, Bohumil; Švecová, Magdalena; Duška, František; Grünerová-Lippertová, Marcela; Urban, Tomáš; Waldauf, Petr; Zajíček, Robert (Burns, 2024)
INTRODUCTION: Patients who have sustained extensive burns frequently exhibit substantial damage to skeletal muscle and associated complications. The rehabilitation of these patients can be challenging due to the nature of the injury and the subsequent complications. Nevertheless, there is a possibility that functional proprioceptive stimulation (illusory movements) may facilitate effective rehabilitation in patients with limited physiotherapy options. Nevertheless, this approach has yet to be tested in patients with burn injuries. MATERIAL AND METHODOLOGY: A prospective, randomised, crossover trial was conducted at a burn centre in a tertiary teaching hospital. The objective was to assess the effects of illusory movements on energy metabolism, insulin sensitivity, and skeletal muscle biology in adult critically ill patients with deep burns covering 30 % or more of the total body surface area. Two 30-minute daily sessions of functional proprioceptive stimulation were administered in addition to the standard physical therapy or physical activity regimen. Subsequently, the patients proceeded to the next stage of the trial, which involved a two-week crossover period. MEASUREMENTS AND MAIN RESULTS: Daily indirect calorimetry and calculation of nitrogen balance. Skeletal muscle biopsies from vastus lateralis for high resolution respirometry and euglycemic clamps to assess whole body glucose disposal were performed three times: at baseline and then fortnightly after each intervention period. The intervention was feasible and well tolerated in both early and late stages of burn disease. It did not change energy expenditure (mean change -33 [95 % CI: -292;+227] kcal .24 h-1, p = 0.79), nitrogen balance (+2.0 [95 % CI: -3.1;+7.1] g N .1.73 m-2 BSA .24 h-1), or insulin sensitivity (mean change of insulin-mediated glucose disposal -0.33 [95 % CI: -1.18;+0.53] mmol.h-1). At the cellular level, the intervention increased the capacity of mitochondria to synthesize ATP by aerobic phosphorylation and tended to increase mitochondrial coupling. Functional capacities of fatty acid oxidation and electron transfer chain complexes I, II, and IV were unaffected. CONCLUSIONS: Compared to physical therapy alone, two daily sessions of functional proprioceptive stimulation in addition to usual physical therapy in patients with extensive burns did not change energy expenditure, insulin sensitivity, nitrogen balance, or energy substrate oxidation. At cellular level, the intervention improved the capacity of aerobic phosphorylation in skeletal muscle mitochondria. Clinical effects remain to be demonstrated in adequately powered trials.
Keywords: energetický metabolismus; Young Adult; povrch těla; Insulin Resistance; Male; Physical Therapy Modalities; inzulinová rezistence; popálení; nepřímá kalorimetrie; mladý dospělý; klinické křížové studie; Adult; Muscle, Skeletal; Prospective Studies; dospělí; mužské pohlaví; Calorimetry, Indirect; Body Surface Area; kosterní svaly; lidé; Energy Metabolism; ženské pohlaví; Humans; techniky fyzikální terapie; Proprioception; Cross-Over Studies; Burns; propriocepce; Female; lidé středního věku; Middle Aged; prospektivní studie